Population structure of leishmania tropica causing anthroponotic cutaneous leishmaniasis in southern Iran by PCR-RFLP of kinetoplastid DNA - Ghatee, M; Mirhendi, H; Marashifard, M; Kanannejad, Z; Taylor, W; Sharifi, I (Hindawi Publishing Corporation, 2018)
Iran is one of the six countries with the most cutaneous leishmaniasis (CL) patients. Understanding better the genotypes of the parasite population in relation to geography and climate is critical to achieving better CL control. We aimed to characterise the population structure of Leishmania tropica, the cause of anthroponotic cutaneous leishmaniasis (ACL), from important foci in southeast (Bam and Kerman) and southwest (Shiraz) Iran. A total of 39 L. tropica isolates from ACL patients from southeast (Bam 14, Kerman 12) and southwest (Shiraz 13) Iran were analysed by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) of the kinetoplast DNA (kDNA) using restriction enzymes MspI (HpaII) and ClaI. 37 genotypes were identified among south Iran L. tropica isolates. The unweighted pair group method with arithmetic mean (UPGMA) tree obtained from the banding patterns of ClaI digested kDNA RFLP distinguished southeast from and southwest L. tropica isolates with some subclustering but the MspI derived tree showed greater discrimination with greater subclustering and divergence of the two foci of southeast region but with some overlapping. Although a monophyletic structure has been defined for southeast L. tropica, isolates from two foci of southeast Iran were partly discriminated in the current study.